Inorganic Molding
Patent Information
- Application Number
- JP2020194219
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-24
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2040-11-24
AI Technical Summary
【0013】 本発明によれば、高温で熱変形しにくい無機質成形体が提供される。
Smart Images

Figure 0007645067000001 
Figure 0007645067000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an inorganic molded body. [Background technology]
[0002] Conventionally, firing has been performed in industrial furnaces to heat-treat electronic components, battery electrode materials, etc. Furnace materials (insulating materials) installed inside industrial furnaces are required to have low heat capacity and low thermal conductivity. By using such furnace materials, the thermal energy during heating can be efficiently utilized, and the tact time can be shortened to improve production efficiency.
[0003] In this regard, Patent Document 1 describes an inorganic molded body that, when used as a furnace material, has sufficiently low heat capacity and thermal conductivity, sufficient strength, reduced erosion by alkaline gas, and can suppress the occurrence of peeling and cracks on the surface. The inorganic molded body contains alumina fibers, alumina particles, and an inorganic binder, and has an air flow resistivity of 6×10 according to ASTM C522. 5 Pa·S / m 2 Bulk density is 100-200kg / m or less. 3 The present invention describes an inorganic molding in which [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2010-155733 A Summary of the Invention [Problem to be solved by the invention]
[0005] On the other hand, some industrial furnaces require high-temperature firing, and therefore require furnace materials that are less likely to deform when heated. In this regard, there have been conventional furnace materials that contain, in addition to crystalline alumina fibers and alumina particles, refractory ceramic fibers, which are amorphous alumina silica fibers, primarily for the purpose of reducing costs.
[0006] However, the inventors of the present invention independently conducted research and found that refractory ceramic fiber-containing refractory materials have a relatively large amount of creep at high temperatures, and when heavy objects are placed on them, the refractory materials are easily damaged and need to be replaced frequently. In addition, when heater wires are embedded in the refractory materials and used as panel heaters, the heater wires are easily subjected to loads due to the large amount of thermal deformation.
[0007] The present invention has been made in view of the above problems, and one of its objects is to provide an inorganic molded article that is resistant to thermal deformation at high temperatures. [Means for solving the problem]
[0008] The inorganic molded body according to one embodiment of the present invention for solving the above problems is an inorganic molded body that includes alumina fibers having an alumina content of more than 60 mass%, alumina particles, and an inorganic binder, and is substantially free of refractory ceramic fibers, thereby reducing the amount of thermal creep. According to the present invention, an inorganic molded body that is resistant to thermal deformation at high temperatures is provided.
[0009] The inorganic molded body has a thermal creep amount measured in a thermal creep test in which a 10 g weight having a rectangular parallelepiped shape of 30 mm in length and 45 mm in width is placed on the longitudinal center of a flat plate-shaped specimen having a length of 150 mm, a width of 45 mm, and a thickness of 7 mm, and the specimen is held at 1400° C. for 3 hours. The thermal creep amount is measured in accordance with the following (a) or (b): (a) the bulk density of the inorganic molded body and the specimen is 300 kg / m 3 (b) the bulk density of the inorganic molded body and the test body is 300 kg / m 3 or more, and the thermal creep amount is 3.0 mm or less.
[0010] The inorganic molded body has a thermal creep amount / bulk density ratio, which is obtained by dividing the thermal creep amount measured in a thermal creep test in which a flat plate-shaped test specimen having a length of 150 mm, a width of 45 mm, and a thickness of 7 mm is placed on the longitudinal center of the test specimen and held at 1400° C. for 3 hours, by the bulk density of the test specimen, and the ratio satisfies the following (c) or (d): (c) the bulk density of the inorganic molded body and the test specimen is 300 kg / m 3 (d) the bulk density of the inorganic molded body and the test piece is less than 300 kg / m 3 or more, and the thermal creep amount / bulk density ratio is 0.0080 or less.
[0011] The inorganic molded body is a flat plate-shaped test piece having a length of 150 mm, a width of 50 mm and a thickness of 25 mm that has not been heated at a temperature of 200° C. or more. The maximum load measured in the bending strength test is applied at a head speed of 10 mm / min using a three-point bending strength tester. The formula for the unheated bending strength (MPa) is: (3×maximum load (N)×distance between lower supports (mm)) / (2×width of test piece (mm)×thickness of test piece (mm)). 2}; by the bulk density of the test specimen, the ratio of unheated bending strength to bulk density may be 0.0031 or more.
[0012] The inorganic molded body may have a content of the refractory ceramic fiber of 0.1 parts by mass or less per 100 parts by mass of the inorganic molded body. The inorganic molded body may have an average particle size of the alumina particles of 0.5 μm or more and 100 μm or less. The inorganic molded body may have a bulk density of 100 kg / m 3 More than 1000kg / m 3 The inorganic molded body may further include a heater wire. Effect of the Invention
[0013] According to the present invention, there is provided an inorganic molded article that is resistant to thermal deformation at high temperatures. [Brief description of the drawings]
[0014] [Figure 1] FIG. 2 is an explanatory diagram showing an example of the results of evaluating the physical properties of an inorganic molded body in one embodiment of the present invention. [Diagram 2] FIG. 4 is an explanatory diagram showing another example of the results of evaluating the physical properties of an inorganic molded body in one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] An inorganic molded body according to one embodiment of the present invention (hereinafter, referred to as the present molded body) will be described below, although the present invention is not limited to this embodiment.
[0016] The present molded body is an inorganic molded body that contains alumina fibers having an alumina content of more than 60 mass%, alumina particles, and an inorganic binder, and has a reduced amount of thermal creep due to the fact that it is substantially free of refractory ceramic fibers.
[0017] The alumina fiber is a metal oxide fiber containing alumina as a main component. The alumina fiber contained in the present molded body has an alumina content of more than 60 mass%. The alumina content of the alumina fiber is not particularly limited as long as it is more than 60 mass%, but may be, for example, 61 mass% or more, 65 mass% or more, or 70 mass% or more.
[0018] Furthermore, when the alumina content of the alumina fiber is 70 mass% or more, the alumina content is preferably 72 mass% or more, more preferably 75 mass% or more, even more preferably 80 mass% or more, and particularly preferably 85 mass% or more.
[0019] Furthermore, when the alumina content of the alumina fibers is 85 mass % or more, the alumina content is preferably 90 mass % or more, more preferably 93 mass % or more, and particularly preferably 95 mass % or more.
[0020] The greater the alumina content of the alumina fiber, the smaller the amount of thermal creep of the present molded body containing the alumina fiber. The upper limit of the alumina content of the alumina fiber is not particularly limited, but the alumina content may be, for example, 100% by mass or less, 99% by mass or less, 98% by mass or less, 97% by mass or less, or 96% by mass or less.
[0021] The alumina content of the alumina fiber may be specified by any combination of any of the above lower limits and any of the above upper limits. The present molded body may include two or more types of alumina fiber having different alumina contents, or may include only one type of alumina fiber having a specific alumina content.
[0022] The alumina fiber may further contain a component other than alumina. When the alumina fiber contains a component other than alumina (other component), the other component may be, for example, one or more selected from the group consisting of silica, zirconia, calcia, iron oxide, zodiac, and magnesia, and is preferably silica.
[0023] When the alumina fiber contains silica, the silica content per 100 parts by mass of the content of other components in the alumina fiber (when the alumina fiber contains two or more other components, the total content of the two or more other components) may be, for example, 60 parts by mass or more (60 parts by mass or more and 100 parts by mass or less), preferably 70 parts by mass or more, more preferably 80 parts by mass or more, even more preferably 90 parts by mass or more, and particularly preferably 95 parts by mass or more.
[0024] Specifically, for example, if the alumina content of the alumina fiber is 80 mass% (i.e., the content of other components is 20 mass%) and the silica content per 100 mass parts of the other components is 90 mass parts or more, the silica content in the alumina fiber is 18 mass parts or more and 20 mass parts or less.
[0025] The average length of the alumina fibers is not particularly limited, but is preferably, for example, 100 μm or more and 100,000 μm or less, more preferably 1,000 μm or more and 80,000 μm or less, and particularly preferably 3,000 μm or more and 50,000 μm or less.
[0026] The average fiber diameter of the alumina fibers is not particularly limited, but is preferably, for example, 1 μm or more and 20 μm or less, more preferably 2 μm or more and 10 μm or less, and particularly preferably 3 μm or more and 7 μm or less. The aspect ratio of the alumina fibers is not particularly limited, but is preferably, for example, 25 or more.
[0027] The alumina particles may be made of sintered alumina, but are preferably made of α-alumina (fused alumina) having high crystallinity. The average particle size of the alumina particles is not particularly limited, but is, for example, 0.5 μm or more and 100 μm or more. below It is preferable that the thickness is 0.5 μm or more and 50 μm or less, more preferable that the thickness is 0.5 μm or more and 15 μm or less, and particularly preferable that the thickness is 2.0 μm or more and 10 μm or less.
[0028] The smaller the average particle size of the alumina particles, the higher the mechanical strength of the present molded article containing the alumina particles. The average particle size of the alumina particles is measured by a laser diffraction particle size distribution measuring device.
[0029] The inorganic binder is not particularly limited as long as it does not impair the effects of the present invention. For example, the inorganic binder is preferably one or more selected from the group consisting of colloidal silica (e.g., one or more selected from the group consisting of anionic colloidal silica and cationic colloidal silica), fumed silica, zirconia sol, titania sol, alumina sol, and bentonite, and is particularly preferably colloidal silica.
[0030] The present molded body may further contain an inorganic fixing agent. The inorganic fixing agent is not particularly limited as long as it does not impair the effects of the present invention, but may be, for example, one or more selected from the group consisting of aluminum sulfate, alumina sol, and ammonia water, and is preferably aluminum sulfate.
[0031] The present molded body may further contain an organic binder. The organic binder is not particularly limited as long as it does not impair the effects of the present invention, but is preferably, for example, one or more selected from the group consisting of polymer flocculants and starch. In addition, when the present molded body contains a polymer flocculant, the present molded body may further contain starch or may not contain starch.
[0032] The polymer flocculant as the organic binder is not particularly limited as long as it does not impair the effects of the present invention. For example, it is preferable that the polymer flocculant is one or more selected from the group consisting of polyacrylamide-based polymers, amide-based polymers, polyacrylic ester-based polymers, and polyacrylic ether-based polymers, and is particularly preferably a polyacrylamide-based polymer.
[0033] The starch used as the organic binder is not particularly limited as long as it does not impair the effects of the present invention, and may be, for example, one or more selected from the group consisting of raw starch (e.g., starch derived from a natural raw material (e.g., one or more selected from the group consisting of potato starch, tapioca starch, corn starch, and hydrolysates thereof)), cationic starch, anionic starch, and amphoteric starch.
[0034] The present molded body may further contain, as an organic binder, pulp, a suitable emulsion, etc., as necessary. In producing the present molded body, the type and amount of the organic binder added to the solvent to form flocks of a desired size are optimized depending on the charge amount of the inorganic binder, the nature of the charge, the size of the alumina particles used, etc.
[0035] In addition, it is preferable that the present molded product contains an organic binder at least at the time of molding (for example, at the time when the present molded product is obtained as an inorganic molded product by drying a wet molded product obtained by dehydration molding or papermaking, which will be described later).
[0036] On the other hand, as described below, the present molded body may be subjected to a firing treatment after molding, before shipping, or before use. In the present molded body that has been subjected to the firing treatment, a part or all of the organic binder contained before the firing treatment may be lost.
[0037] The bulk density of the molded product is not particularly limited as long as it does not impair the effects of the present invention. For example, the bulk density is 100 kg / m 3 More than 1000kg / m 3 may be less than 150 kg / m 3 More than 1000kg / m 3 It is preferable that the thickness is less than 200 kg / m 3 More than 1000kg / m 3 More preferably, it is 300 kg / m or less. 3 More than 1000kg / m 3 It is particularly preferred that:
[0038] Here, one of the characteristics of the present molded article is that the present molded article does not substantially contain refractory ceramic fibers (RCF), and therefore the amount of thermal creep is reduced.
[0039] That is, as described above, the inventors of the present invention independently conducted research and found that refractory materials containing RCF have a relatively large amount of creep at high temperatures. In this regard, the present molded product does not substantially contain RCF, and therefore has a reduced amount of thermal creep compared to conventional refractory materials that contain RCF.
[0040] RCF is an amorphous alumina-silica fiber with an alumina (Al2O3) content of 60 mass% or less. Specifically, RCF contains 30 mass% to 60 mass% Al2O3 and 40 mass% to 60 mass% SiO2. RCF further contains 20 mass% or less R n O m (R may contain Zr or Cr). That is, the RCF may contain 0 mass% to 20 mass% R n O m (R may contain Zr or Cr). The average fiber diameter of RCF is generally 1 μm to 3 μm. RCF is produced using a melt fiberization method.
[0041] Specifically, the present molded product, which is substantially free of RCF and has a reduced thermal creep amount, is, for example, substantially free of RCF, and has a thermal creep amount measured in a thermal creep test in which a flat plate-shaped test specimen, which is 150 mm long, 45 mm wide, and 7 mm thick, is placed on the longitudinal center of a 10 g rectangular parallelepiped weight, which is 30 mm long and 45 mm wide, and held at 1400°C for 3 hours, as specified by the following (a) or (b): (a) the present molded product and the test specimen have a bulk density of 300 kg / m 3 (b) the bulk density of the molded body and the test body is 300 kg / m 3 or more, and the thermal creep amount is 3.0 mm or less.
[0042] In the above-mentioned thermal creep test, the present compact is processed to produce a test specimen consisting of the present compact of the above-mentioned size and shape, and the amount of deformation when the test specimen is held at 1400°C for 3 hours while a load of 10 g is applied thereto is measured as the amount of thermal creep.
[0043] When the molded body satisfies the above (a), the bulk density of the molded body and the test specimen is 300 kg / m3 Less than (e.g., 299 kg / m 3 There is no particular limitation as long as the strength is less than 100 kg / m 3 More than 300kg / m 3 may be less than 130 kg / m 3 More than 300kg / m 3 may be less than 150 kg / m 3 More than 300kg / m 3 It may be less than.
[0044] Furthermore, the thermal creep amount of the present molded article satisfying the above (a) is, for example, preferably 8.0 mm or less, more preferably 7.0 mm or less, even more preferably 6.0 mm or less, and particularly preferably 5.0 mm or less.
[0045] Furthermore, when the thermal creep amount of the present molded article satisfying the above (a) is 5.0 mm or less, the thermal creep amount is, for example, preferably 4.0 mm or less, more preferably 3.5 mm or less, and particularly preferably 3.0 mm or less.
[0046] When the molded product satisfies the above (b), the bulk density of the molded product and the test specimen is 300 kg / m 3 There is no particular limitation as long as it is equal to or more than 300 kg / m 3 More than 1000kg / m 3 It may be the following.
[0047] Furthermore, the thermal creep amount of the present molded article that satisfies the above (b) is, for example, preferably 2.5 mm or less, and particularly preferably 2.0 mm or less.
[0048] The present molded product, which has a reduced thermal creep amount due to being substantially free of RCF, is, for example, a molded product that is substantially free of RCF and has a flat plate-shaped test specimen having a length of 150 mm, a width of 45 mm, and a thickness of 7 mm, a 10 g weight having a rectangular parallelepiped shape having a length of 30 mm and a width of 45 mm, and is maintained at 1400°C for 3 hours. The thermal creep amount measured in the thermal creep test is divided by the bulk density of the test specimen, and the ratio of the thermal creep amount to the bulk density is (c) or (d) below: (c) The present molded product and the test specimen have a bulk density of 300 kg / m 3 (d) the bulk density of the molded body and the test body is 300 kg / m or less, and the ratio of the thermal creep amount to the bulk density is 0.0450 or less; 3 or more, and the thermal creep amount / bulk density ratio is 0.0075 or less.
[0049] When the molded product satisfies the above (c), the bulk density of the molded product and the test specimen is 300 kg / m 3 Less than (e.g., 299 kg / m 3 There is no particular limitation as long as the strength is less than 100 kg / m 3 More than 300kg / m 3 may be less than 130 kg / m 3 More than 300kg / m 3 may be less than 150 kg / m 3 More than 300kg / m 3 It may be less than.
[0050] In addition, the thermal creep amount / bulk density ratio of the present molded body satisfying the above (c) may be, for example, 0.0400 or less, preferably 0.0350 or less, more preferably 0.0300 or less, even more preferably 0.0250 or less, and particularly preferably 0.0200 or less.
[0051] When the molded body satisfies the above (d), the bulk density of the molded body and the test specimen is 300 kg / m 3 There is no particular limitation as long as it is equal to or more than 300 kg / m 3 More than 1000kg / m 3 It may be the following.
[0052] In addition, the thermal creep amount / bulk density ratio of the present molded body satisfying the above (d) may be, for example, 0.0075 or less, preferably 0.0070 or less, more preferably 0.0600 or less, even more preferably 0.0500 or less, and particularly preferably 0.0400 or less.
[0053] Furthermore, the present molded article, which has a reduced amount of thermal creep due to being substantially free of RCF, can be calculated based on the maximum load measured in a bending strength test in which a load is applied to a flat plate-shaped test specimen, which is 150 mm long, 50 mm wide, and 25 mm thick and which does not substantially contain RCF and has never been heated at a temperature of 200° C. or higher, using a three-point bending strength tester at a head speed of 10 mm / min, using the formula: unheated bending strength (MPa)={3×maximum load (N)×distance between lower supports (mm)} / {2×width of test specimen (mm)×(thickness of test specimen (mm)) 2}; the unheated bending strength / bulk density ratio obtained by dividing the unheated bending strength obtained by the above by the bulk density of the test specimen may be 0.0031 or more.
[0054] In the above bending strength test, an unheated molded body (one that has not yet been heated to a temperature of 200°C or higher) is processed to produce a test specimen consisting of the molded body of the above size and shape, and the maximum strength (breaking strength) is measured when a load is applied to the test specimen using a three-point bending strength tester at a head speed of 10 mm / min, and the unheated bending strength is calculated using the above formula.
[0055] The unheated bending strength / bulk density ratio of the present molded product is, for example, preferably 0.0035 or more, and particularly preferably 0.0040 or more.
[0056] The present molded product substantially free of RCF is an inorganic molded product having an RCF content of 0.1 parts by mass or less per 100 parts by mass of the present molded product. The RCF content of 100 parts by mass of the present molded product is, for example, preferably 0.07 parts by mass or less, and particularly preferably 0.05 parts by mass or less.
[0057] The content of alumina fibers in the present molded body is not particularly limited as long as it is within a range that does not impair the effects of the present invention, but the present molded body may contain, for example, 15 parts by mass or more and 90 parts by mass or less of alumina fibers, 20 parts by mass or more and 85 parts by mass or less of alumina fibers, 25 parts by mass or more and 80 parts by mass or less of alumina fibers, or 30 parts by mass or more and 75 parts by mass or less of alumina fibers, per 100 parts by mass of the present molded body.
[0058] Furthermore, the present molded body may contain, for example, 10 parts by mass or more and 90 parts by mass or less of alumina-based fibers, 20 parts by mass or more and 90 parts by mass or less of alumina-based fibers, 30 parts by mass or more and 90 parts by mass or less of alumina-based fibers, or 40 parts by mass or more and 80 parts by mass or less of alumina-based fibers, relative to 100 parts by mass of the total of the content of alumina-based fibers and the content of alumina particles.
[0059] The content of alumina particles in the present molded body is not particularly limited as long as it is within a range that does not impair the effects of the present invention, but the present molded body may contain, for example, 5 parts by mass or more and 65 parts by mass or less of alumina particles, 10 parts by mass or more and 60 parts by mass or less of alumina particles, or 15 parts by mass or more and 55 parts by mass or less of alumina particles, per 100 parts by mass of the present molded body.
[0060] The compact has a bulk density of 300 kg / m 3 When the content of alumina fibers having an alumina content of 72 mass% or less relative to the total 100 parts by mass of the content of alumina fibers and the content of alumina particles is less than 40 mass%, or less than 35 mass%, or less than 20 mass%, or less than 10 mass%.
[0061] The molded product has a bulk density of 300 kg / m 3When it is less than 72 mass%, the alumina fiber contained in the present molded body may have an alumina content of more than 72 mass%, 75 mass% or more, or 80 mass% or more.
[0062] The compact has a bulk density of 300 kg / m 3 If this is the case, the content of alumina fibers having an alumina content of 72 mass% or less relative to 100 parts by mass of the total of the alumina fiber content and the alumina particle content may be less than 60 mass%, may be 55 mass% or less, may be 50 mass% or less, may be 45 mass% or less, or may be 40 mass% or less.
[0063] The content of the inorganic binder in the present molded body is not particularly limited as long as it is within a range that does not impair the effects of the present invention, but the present molded body preferably contains, for example, 1 part by mass or more and 20 parts by mass or less of the inorganic binder per 100 parts by mass of the total of the content of the alumina fibers and the content of the alumina particles, more preferably contains 3 parts by mass or more and 17 parts by mass or less of the inorganic binder, and particularly preferably contains 5 parts by mass or more and 15 parts by mass or less of the inorganic binder.
[0064] When the present molded body contains an inorganic fixing material, the content of the inorganic fixing material in the present molded body is not particularly limited as long as it is within a range that does not impair the effects of the present invention. However, the present molded body preferably contains, for example, 0.1 part by mass or more and 15 parts by mass or less of the inorganic fixing material relative to 100 parts by mass of the total of the content of the alumina fibers and the content of the alumina particles, more preferably contains 0.1 part by mass or more and 10 parts by mass or less of the inorganic fixing material, and particularly preferably contains 0.1 part by mass or more and 5 parts by mass or less of the inorganic fixing material.
[0065] When the present molded body contains an organic binder, the content of the organic binder in the present molded body is not particularly limited as long as it is within a range that does not impair the effects of the present invention; however, the present molded body preferably contains, for example, 0.1 part by mass or more and 15 parts by mass or less of the organic binder per 100 parts by mass of the total of the content of the alumina fibers and the content of the alumina particles, more preferably contains 0.5 parts by mass or more and 10 parts by mass or less of the organic binder, and particularly preferably contains 1 part by mass or more and 5 parts by mass or less of the organic binder.
[0066] The present molded article preferably has a sufficiently low thermal conductivity to function as a thermal insulator. That is, the present molded article preferably has a thermal conductivity at 600°C of, for example, 0.45 (W / m K) or less, more preferably 0.35 (W / m K) or less, and particularly preferably 0.25 (W / m K) or less.
[0067] The present molded body may include a heater wire. That is, in this case, the present molded body includes, for example, a heater wire arranged on its surface. The present molded body including the heater wire is used, for example, as a panel heater. The heater wire is not particularly limited, but is preferably, for example, a metal wire (for example, a nichrome wire or molybdenum disilicide) that generates heat when electricity is applied thereto.
[0068] The present molded body is preferably manufactured by the following method. In the manufacturing method of the present molded body, a slurry containing the above-mentioned alumina fibers, alumina particles, and an inorganic binder is first prepared. At this time, a slurry further containing an inorganic fixing agent may be prepared. Also, a slurry further containing an organic binder may be prepared.
[0069] The wet volume of the slurry is not particularly limited as long as it is within a range that does not impair the effects of the present invention, but is preferably, for example, 50 mL / 20 g or more and 1000 mL / 20 g or less, more preferably 75 mL / 20 g or more and 950 mL / 20 g or less, and particularly preferably 100 mL / 20 g or more and 900 mL / 20 g or less.
[0070] The slurry is then dehydrated and molded or paper-formed to obtain a wet molded body. If necessary (for example, when producing a main molded body having a relatively high bulk density), the wet molded body may be pressed.
[0071] Thereafter, the wet compact is dried to obtain an inorganic compact (the present compact). The shape of the present compact is not particularly limited, but is preferably, for example, a board, sheet, or block shape. The shape of the present compact can also be cylindrical, conical, or other shapes by selecting a suction mold according to the desired shape.
[0072] The present molded article may be further subjected to a firing treatment. That is, for example, when the present molded article is used as a heat insulating material or a fireproof material, the present molded article may be subjected to a firing treatment before shipment, before use, or during use.
[0073] The method of the firing process is not particularly limited, and for example, the firing process is performed using a known heating furnace. The firing temperature is not particularly limited as long as it is within a range that does not impair the effects of the present invention, but is preferably, for example, 600°C or higher (for example, 600°C or higher and 1600°C or lower). The firing time is not particularly limited as long as it is within a range that does not impair the effects of the present invention, but is preferably, for example, 30 minutes or more (for example, 30 minutes or more and 60 minutes or less).
[0074] The present molded body may be subjected to a curing treatment. The curing treatment is, for example, a treatment in which the present molded body is impregnated with a curing treatment liquid containing an inorganic binder (for example, one or more selected from the group consisting of colloidal silica and alumina sol) and dried. The curing treatment can effectively improve the hardness of the present molded body after drying.
[0075] The hardening treatment liquid may contain, in addition to an inorganic binder, one or more selected from the group consisting of an organic thickener for controlling viscosity and inorganic powders (e.g., one or more selected from the group consisting of glass powder, alumina powder, and wollastonite powder). The method for impregnating the molded body with the hardening treatment liquid is not particularly limited, but for example, one or more selected from the group consisting of brush coating, spray coating, and immersion are preferably used.
[0076] The molded body may be subjected to a surface coating treatment. That is, for example, by coating the surface of the molded body with a coating agent containing ZrO2, SiO2 and SiC4 or a coating agent containing Al2O3 and SiO2, the surface properties of the molded body can be effectively improved. Specifically, for example, when the molded body is placed in a furnace for use, the surface coating treatment of the molded body can effectively improve the corrosion resistance against scale (e.g., iron oxide) in the furnace and / or the wind speed resistance against hot air in the furnace.
[0077] The present molded body may be subjected to an adhesive treatment. That is, for example, when a plurality of the present molded bodies are to be bonded to each other or when the present molded body is to be bonded to another molded body, the adhesive strength can be effectively improved by applying an adhesive containing Al2O3 and SiO2 or an adhesive containing Fe and SiO2 to the bonding surface of the present molded body.
[0078] In addition, when manufacturing a present molded body containing a heater wire (for example, a present molded body that is a panel heater), for example, the heater wire may be placed in a mold beforehand during suction molding so that the heater wire is contained inside the wet molded body, or the present molded body may be cut to embed the heater wire in the cut portion, and a lid may be further provided. According to the former method, the heater wire has a high retention force and is less likely to come into contact with the object to be heated. According to the latter method, the present molded body containing the heater wire is easy to manufacture and has high thermal efficiency. In addition, in the latter method, the above-mentioned hardening treatment is applied to the cut surface of the present molded body before embedding the heater wire, thereby improving handleability. Furthermore, since the present molded body has a high strength, the processing accuracy during cutting is improved.
[0079] Next, a specific example according to this embodiment will be described. EXAMPLES
[0080] [Raw material] As inorganic fibers, (I) alumina fiber having an alumina content of 95% by mass (manufactured by Denka Co., Ltd., "B95N5", silica content 5% by mass, α-alumina content in alumina 50% by mass to 59% by mass, average fiber diameter 2 μm to 4 μm), (II) alumina fiber having an alumina content of 80% by mass (manufactured by Denka Co., Ltd., "B80", silica content 20% by mass, mullite content in alumina 50% by mass to 70% by mass, average fiber diameter 2 μm to 4 μm), The fibers used were (III) alumina fibers with an alumina content of 72 mass% ("MAFTEC" manufactured by Mitsubishi Chemical Corporation, silica content 28 mass%, mullite content in alumina 0 mass% to 59 mass%, average fiber diameter 5 μm to 7 μm), and (V) RCF ("Fineflex 1300" manufactured by Nichias Corporation, alumina content 49 mass%, silica content 51 mass%, average fiber diameter 2 μm to 3 μm).
[0081] Alumina particles (manufactured by Nippon Light Metal Co., Ltd., "SA31", average particle size 5 μm, Al 2 O 3 : 99.4% or more) were used as the inorganic particles.
[0082] As the inorganic binder, colloidal silica (manufactured by Nippon Chemical Industry Co., Ltd., "Silicadol 30", suspension with 30% solids by mass, average particle size of solids of 15 nm, pH 10.0) and alumina sol (manufactured by Nissan Chemical Industries, Ltd., "Aluminasol 520", suspension with 20% solids by mass, pH 4.0) were used.
[0083] The inorganic fixing agent used was aluminum sulfate (Asada Chemical Industry Co., Ltd.'s "Liquid Aluminum Sulfate", aluminum oxide 8.0-8.2%, pH 3.0 or higher). The organic binder used was a polymer flocculant, polyacrylamide (Arakawa Chemical Industry Co., Ltd.'s "Polystron 705", cationic, non-volatile content 10%, pH 2.5-3.5, viscosity 300-1000 mPa s), and starch (Nippon Starch Chemical Co., Ltd.'s "Petrosize J").
[0084] [Inorganic Molded Body] In the composition shown in Fig. 1 and Fig. 2, inorganic fibers, inorganic particles, inorganic binder, inorganic fixing agent, and organic binder are added to water, and the slurry concentration is 2% by mass Water was added and stirred so as to obtain a slurry.
[0085] The slurry obtained as described above was poured into a mold with a net installed at the bottom, and dehydrated and molded by a suction dehydration molding method in which the solvent was sucked out, to obtain a wet molded body having a plate shape. Furthermore, in Examples 8 to 14 and Comparative Example 3, the wet molded body obtained as described above was pressed so that the bulk density of the inorganic molded body finally obtained would be within a desired range. On the other hand, in Examples 1 to 7 and Comparative Examples 1 and 2, the wet molded body was not pressed. Thereafter, the wet molded body obtained in each example was dried in a dryer at 110°C for 36 hours to obtain a plate-shaped inorganic molded body having a thickness of 25 mm.
[0086] [Bulk density] The bulk density of the inorganic molded body obtained in each example was calculated by measuring the dimensions (length, width, thickness) with a vernier caliper and measuring the weight with an electronic balance.
[0087] [Unheated bending strength] The unheated bending strength of the inorganic molded body obtained in each example was measured as follows: A load was applied to a flat plate-shaped test piece made of the inorganic molded body, 150 mm long, 50 mm wide, and 25 mm thick, at a head speed of 10 mm / min, using a universal strength tester (Shimadzu Corporation, "Autograph"), and the maximum load (breaking load) was measured.
[0088] The unheated bending strength of the inorganic molded body was calculated by the following formula: Unheated bending strength (MPa) = {3 x maximum load (N) x distance between lower supports (mm)} / {2 x width of specimen (mm) x thickness of specimen (mm)} 2}.
[0089] [Heat shrinkage rate] A flat plate-shaped test piece made of the inorganic molded body obtained in each example, 150 mm long, 50 mm wide, and 25 mm thick, was heated at 1400°C for 24 hours or 1600°C for 24 hours, and the heat shrinkage rate (%) was calculated by the following formula: {test piece length before heating (mm) - test piece length after heating (mm)} / test piece length before heating (mm) x 100. The test piece length was measured using a vernier caliper.
[0090] [Thermal creep amount] The thermal creep amount of the inorganic molded body obtained in each example was measured by the following thermal creep test. That is, first, both ends in the longitudinal direction of a flat plate-shaped specimen made of an inorganic molded body, 150 mm in length, 45 mm in width, and 7 mm in thickness, were supported by a pair of support members (30 mm high) arranged with a gap of 120 mm in the longitudinal direction of the specimen.
[0091] Next, a weight having a rectangular parallelepiped shape of 30 mm in length and 45 mm in width and weighing 10 g or 30 g was placed on the center of the test specimen in the longitudinal direction. Note that the test specimen did not bend at all when the weight was placed on it at room temperature.
[0092] The specimen with the weight placed on it was then heated and held at 1400°C, 1500°C or 1600°C for 3 hours or 24 hours. The specimen was warped by the heating, and the central part of the specimen in the longitudinal direction was displaced downward. The amount of displacement (warping) by the heating was measured as the amount of thermal creep (mm).
[0093] [Results] Figure 1 shows that the bulk density is 150 kg / m 3 ~257kg / m 3 Regarding the inorganic molded bodies (Examples 1 to 7 and Comparative Examples 1 and 2), and in FIG. 2, the bulk density is 319 kg / m 3 ~380kg / m 3 The contents of each component (inorganic fiber, inorganic particle, inorganic binder, inorganic fixing agent, and organic binder) and the measurement results of physical properties are shown for the inorganic molded bodies (Examples 8 to 14 and Comparative Example 3). In Fig. 1 and Fig. 2, the parts by mass of the inorganic binder are shown as solid content equivalents. In Fig. 1 and Fig. 2, the symbol "-" indicates that the physical properties were not measured.
[0094] As shown in FIG. 1, when a load of 10 g was applied at 1400° C. for 3 hours, the thermal creep amount B of the inorganic molded bodies of Examples 1 to 5 was 2.2 mm to 2.7 mm, which was significantly smaller than that of Comparative Examples 1 and 2 (9.2 mm to 13.1 mm).
[0095] Furthermore, the thermal creep amount B / bulk density ratios obtained by dividing the thermal creep amount B of the inorganic molded bodies of Examples 1 to 5 by the bulk density were 0.0086 to 0.0173, which were significantly smaller than those of Comparative Examples 1 and 2 (0.0460 to 0.0649).
[0096] Furthermore, when a load of 10 g was applied at 1600° C. for 3 hours, the thermal creep amounts D of the inorganic molded bodies of Examples 1 to 3 and 5 were 12.5 mm to 29.5 mm, which were significantly smaller than that of Comparative Example 1 (36.0 mm).
[0097] Moreover, the thermal creep amount D / bulk density ratios of the inorganic molded bodies of Examples 1 to 3 and 5 were 0.0537 to 0.1612, which were significantly smaller than that of Comparative Example 1 (0.1800).
[0098] Moreover, the ratio of unheated bending strength to bulk density of the inorganic molded bodies of Examples 1 to 3 was 0.0042 to 0.0061, which was significantly larger than that of Comparative Examples 1 and 2 (0.0025 to 0.0030).
[0099] As shown in FIG. 2, the thermal creep amounts B of the inorganic molded bodies of Examples 8 to 12 were 0.9 mm to 1.4 mm, which was significantly smaller than that of Comparative Example 3 (3.1 mm) and smaller than that of Examples 1 to 5 (2.2 mm to 2.7 mm).
[0100] Moreover, the thermal creep amount B / bulk density ratios of the inorganic molded bodies of Examples 8 to 14 were 0.0028 to 0.0039, which was significantly smaller than that of Comparative Example 3 (0.0082) and that of Examples 1 to 5 (0.0086 to 0.0173).
[0101] Moreover, the thermal creep amount D of the inorganic molded bodies of Examples 8 to 14 was 7.4 mm to 18.5 mm, which was significantly smaller than that of Comparative Example 3 (21.0 mm).
[0102] The thermal creep amount D / bulk density ratio of the inorganic molded bodies of Examples 8 to 10 and 12 was 0.0219 to 0.0486, and the comparative 3 (0.0553) and those of Examples 1 to 3 and 5 (0.0537 to 0.1612).
[0103] Furthermore, when a load of 30 g was applied at 1400° C. for 3 hours, the thermal creep amount A of the inorganic molded bodies of Examples 10, 12 and 14 was 2.0 mm to 2.6 mm, which was significantly smaller than that of Comparative Example 3 (18.0 mm).
[0104] Moreover, the thermal creep amount A / bulk density ratios of the inorganic molded bodies of Examples 10, 12, and 14 were 0.0054 to 0.0070, which was significantly smaller than that of Comparative Example 3 (0.0474).
[0105] Furthermore, the thermal creep amounts C of the inorganic molded bodies of Examples 10, 12 and 14 when a load of 10 g was applied at 1500° C. for 3 hours were 3.7 mm to 3.9 mm, which was significantly smaller than that of Comparative Example 3 (16.5 mm).
[0106] Moreover, the thermal creep amount C / bulk density ratios of the inorganic molded bodies of Examples 10, 12, and 14 were 0.0100 to 0.0108, which was significantly smaller than that of Comparative Example 3 (0.0434).
[0107] Furthermore, when a load of 10 g was applied at 1400° C. for 24 hours, the thermal creep amount E of the inorganic molded bodies of Examples 10, 12 and 14 was 2.8 mm to 3.5 mm, which was significantly smaller than that of Comparative Example 3 (13.5 mm).
[0108] Moreover, the thermal creep amount E / bulk density ratios of the inorganic molded bodies of Examples 10, 12, and 14 were 0.0076 to 0.0097, which was significantly smaller than that of Comparative Example 3 (0.0355).
[0109] Furthermore, the thermal creep amounts F of the inorganic molded bodies of Examples 10, 12 and 14 when a load of 10 g was applied at 1600° C. for 24 hours were 20.5 mm to 30.5 mm, which was significantly smaller than that of Comparative Example 3 (37.0 mm).
[0110] Moreover, the thermal creep amount F / bulk density ratios of the inorganic molded bodies of Examples 10, 12, and 14 were 0.0554 to 0.0824, which were significantly smaller than that of Comparative Example 3 (0.0974).
[0111] Moreover, the ratio of unheated bending strength to bulk density of the inorganic molded articles of Examples 8 to 10 and 12 was 0.0057 to 0.0071, which was significantly larger than that of Comparative Example 3 (0.0019).
[0112] Moreover, the thermal shrinkage rates of the inorganic molded bodies of Examples 8 to 12 when heated at 1400° C. for 24 hours were 0.3%, which was significantly smaller than that of Comparative Example 3 (0.9%).
Claims
1. An alumina fiber having an alumina content of more than 60 mass%; Alumina particles having an average particle size of 0.5 μm or more and 100 μm or less; An inorganic binder; A molded body comprising: The alumina fiber is contained in an amount of 10 parts by mass or more and 90 parts by mass or less relative to 100 parts by mass of the total content of the alumina fiber and the alumina particle, The content of amorphous alumina-silica fiber having an alumina content of 60% by mass or less is 0.1 parts by mass or less relative to 100 parts by mass of the molded body; The thermal creep amount measured in a thermal creep test is determined by placing a 10 g weight having a rectangular parallelepiped shape of 30 mm in length and 45 mm in width on the longitudinal center of a flat plate-shaped test specimen having a length of 150 mm, a width of 45 mm, and a thickness of 7 mm, which is produced by processing the molded body, and maintaining the weight at 1400° C. for 3 hours. The thermal creep amount is determined as follows: (a) the bulk density of the compact and the test specimen is less than 300 kg / m 3 , and the thermal creep amount is 9.0 mm or less; (b) the bulk density of the molded body and the test specimen is 300 kg / m 3 or more, and the thermal creep amount is 3.0 mm or less; Fulfilling A flexural strength test is performed by applying a load to a flat plate-shaped test specimen having a length of 150 mm, a width of 50 mm, and a thickness of 25 mm, which is produced by processing the molded body that has never been heated at a temperature of 200° C. or higher, using a three-point bending strength tester at a head speed of 10 mm / min. The unheated bending strength is calculated based on the maximum load measured in the flexural strength test, and the unheated bending strength is calculated by the formula: unheated bending strength (MPa) = {3 x maximum load (N) x distance between lower supports (mm)} / {2 x width (mm) x thickness (mm) of test specimen) 2}; and the unheated bending strength / bulk density ratio obtained by dividing the unheated bending strength by the bulk density of the test specimen is 0.0035 or more. Molded bodies (however, excluding alkaline earth silicate fibers, silicon carbide particles, and silicon nitride particles).
2. The molded body is processed to prepare a flat plate-shaped test specimen having a length of 150 mm, a width of 45 mm, and a thickness of 7 mm. A 10 g rectangular weight having a length of 30 mm and a width of 45 mm is placed on the longitudinal center of the test specimen and kept at 1400°C for 3 hours. The thermal creep amount measured in the thermal creep test is divided by the bulk density of the test specimen to obtain a thermal creep amount / bulk density ratio that satisfies the following (c) or (d): (c) The bulk density of the molded body and the test body is 300 kg / m 3 and the thermal creep amount / bulk density ratio is 0.0450 or less; (d) The bulk density of the molded body and the test body is 300 kg / m 3 or more, and the thermal creep amount / bulk density ratio is 0.0080 or less; The molded article according to claim 1 , which satisfies the above.
3. The alumina fiber is contained in an amount of 15 parts by mass or more and 90 parts by mass or less relative to 100 parts by mass of the molded body. The molded article according to claim 1 or 2.
4. The alumina particles are contained in an amount of 5 parts by mass or more and 65 parts by mass or less relative to 100 parts by mass of the molded body. The molded article according to any one of claims 1 to 3.
5. The inorganic binder is contained in an amount of 1 part by mass or more and 20 parts by mass or less per 100 parts by mass of the total content of the alumina fiber and the alumina particle, The molded article according to any one of claims 1 to 4.
6. Bulk density is 100 kg / m 3 More than 1000kg / m 3 Below is the The molded article according to any one of claims 1 to 5.
7. The thermal conductivity at 600°C is 0.45 (W / m K) or less. The molded article according to any one of claims 1 to 6.
8. Further comprising a heater wire, The molded article according to any one of claims 1 to 7.
Citation Information
Patent Citations
Formed material of inorganic fiber having high heat-resistance
JP1997208318A
Inorganic molded body
JP2010155733A
Inorganic molded body
JP2010159190A
Inorganic fibrous molded body
JP2018199879A
Furnace wall component
WO2007052338A1